Oxygen Uptake in Maximal Effort Constant Rate and Interval Running - Daniel Pratt; Brendan J. O'Brien; Bradley Clark (The Scientific World Journal)
This study investigated differences in average of maximal effort interval running to maximal effort constant rate running at lactate threshold matched for time. The average and distance covered of 10 recreational male runners (: 4158 ± 390 mL·min−1) were compared between a maximal effort constant-rate run at lactate threshold (CRLT), a maximal effort interval run (INT) consisting of 2 min at speed with 2 minutes at 50% of repeated 5 times, and a run at the average speed sustained during the interval run (CR submax). Data are presented as mean and 95% confidence intervals. The average for INT, 3451 (3269–3633) mL·min−1, 83% , was not significantly different to CRLT, 3464 (3285–3643) mL·min−1, 84% , but both were significantly higher than CR sub-max, 3464 (3285–3643) mL·min−1, 76% . The distance covered was significantly greater in CLRT, 4431 (4202–3731) metres, compared to INT and CR sub-max, 4070 (3831–4309) metres. The novel finding was that a 20-minute maximal effort constant rate run uses similar amounts of oxygen as a 20-minute maximal effort interval run despite the greater distance covered in the maximal effort constant-rate run.